Shift rotation, circadian misalignment and excessive body weight influence psychomotor performance: a prospective and observational study under real life conditions - Rosa, Dayane Eusenia (Sci Rep, 2019)
We aimed to evaluate the influence of shift work rotation, circadian misalignment and being overweight/obese on psychomotor performance throughout a complete shift rotation schedule. The study was conducted with 30 males working rotating shifts from a mining company under real life conditions. Individuals were evaluated over seven days in a shift schedule carried out as follow: two shifts in the morning (D1 and D2), two shifts in the afternoon (D3 and D4), 24 hour free day (D5) and two shifts at night (D6 and D7). Work performance was evaluated by psychomotor vigilance task tests (PVT), and actigraphy was used to characterise the rest-activity rhythm based on intradaily variability (IV) and interdaily stability (IS) of nonparametric functions. We found a significant effect of the shift, body mass index (BMI), IS and IV on lapses in attention. More lapses occurred on D7 than D1, D2, D3 and D4 of the schedule shift. The obese group presented a higher number of lapses in attention than eutrophic. The interaction between day and IS showed that less synchronised individuals presented a higher number of lapses in attention on D7 than D1 and, for the interaction between day and IV, more fragmented individuals presented a higher number of lapses in attention on D7 than D6. We conclude that higher BMI, lower synchronisation and higher fragmentation of the rest-activity pattern influenced lapses in attention throughout the shift rotation.